2015
DOI: 10.1108/md-06-2014-0402
|View full text |Cite
|
Sign up to set email alerts
|

Should retail trade companies avoid recruiting maximisers?

Abstract: Purpose -Investigates differences in characteristics, job outcome experiences and attitudes of maximiser and satisficer decision-making style groups working in the retail trade.Design/methodology/approach -Survey conducted using the Amazon Mechanical Turk panel of 140 US participants who have accepted a retail job offer in the past six months. Investigated participants' decision-making style, plus experiences and attitudes toward their present job and the (retail) job information sources used. Findings -The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 50 publications
1
16
0
Order By: Relevance
“…In line with the literature [20,55,72,102], we have shown that maximizers perform more intensive decision making processes compared to satisficers. In order to make a purchase decision, they consider a larger number of alternatives and compare them all against a larger set of criteria.…”
Section: Hypothesis Testingsupporting
confidence: 75%
“…In line with the literature [20,55,72,102], we have shown that maximizers perform more intensive decision making processes compared to satisficers. In order to make a purchase decision, they consider a larger number of alternatives and compare them all against a larger set of criteria.…”
Section: Hypothesis Testingsupporting
confidence: 75%
“…They put a lot of effort into searching, checking and comparing job information, tending to adopt a central processing route, which leads them to cautiously weigh and evaluate the information (Petty and Cacioppo, 1984). From a risk-aversion viewpoint (Pratt, 1964), compared to satisficers, maximisers have a significantly higher level of uncertainty avoidance (Liu et al, 2015). Maximisers work hard to lower the risk of making a bad decision by comparing all information and options (Polman, 2012).…”
Section: Tie Strength Message Valence and Decision-making Stylementioning
confidence: 99%
“…Maximizers consider more information and evaluation criteria, so a message with added detail is more likely to help them understand the positive perspectives of the position or company. From a risk‐aversion viewpoint (Pratt, ), as highlighted earlier, compared to satisficers, maximizers have a significantly higher level of uncertainty avoidance (Liu et al, ). They work hard to lower the risk of making a bad decision by comparing all information and options (Polman, ); therefore, they more cautiously weigh the information content (Cacioppo, Petty, & Morris, ).…”
Section: Literature Reviewmentioning
confidence: 94%
“…Maximizers hold high standards and have more criteria regarding the outcomes of the decisions they make, but they also find it challenging to make a decision. Liu, Keeling, and Papamichail () showed that maximizers always aim to get the best result and have a significantly higher need for uncertainty avoidance, which leads them to put a greater deal of effort and resources into searching for more in‐depth and diverse information together with a greater number of searches regarding the analysis of information before making a decision.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation